2020
DOI: 10.1080/26408066.2019.1617213
|View full text |Cite
|
Sign up to set email alerts
|

Family as the Conduit to Promote Indigenous Women and Men’s Enculturation and Wellness: “I Wish I Had Learned Earlier”

Abstract: The purpose of this article is to explore how food and other cultural traditions promote wellness, cultural continuity, enculturation, and family resilience within tribal communities in the U.S. Using the Framework of Historical Oppression, Resilience, and Transcendence (FHORT), this critical ethnography examines Indigenous peoples' perspectives on and experiences with food and cultural traditions. Thematic analysis of data from 436 participants (approximately 2/3 rds of which were women) across two Southeaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…Twenty-eight studies in this review reported on the wellbeing of Indigenous youth in the USA [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Our thematic analysis identified six overarching components of wellbeing for this population: safety and basic needs; relationships and connection; cultural identity and pride; looking to the past and the future; and being healthy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-eight studies in this review reported on the wellbeing of Indigenous youth in the USA [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Our thematic analysis identified six overarching components of wellbeing for this population: safety and basic needs; relationships and connection; cultural identity and pride; looking to the past and the future; and being healthy.…”
Section: Resultsmentioning
confidence: 99%
“…Connections with community, family, Elders and peers are key contributing factors to how Indigenous youth develop a sense of self and feelings of belonging [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 127 , 128 , 129 , 130 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Feeling part of a community, for youth, is fostered through engagement with traditional cultural activities that instil pride and identity [ 117 , 120 , 123 , 125 , 129 , 132 , 133 , 134 , 135 , 137 , 138 , 139 , 140 , 143 , 144 ]. Participation as a community member is often centrally important in developing Indigenous youths’ identity [ 124 , 133 , 139 , 142 , 143 ] and resilience [ 127 ,...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural activity groups (e.g. painting, dancing, basket-weaving, or cooking) may also help participants meet basic psychological needs and build resilience [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family resilience enables families' successful coping under duress; a recent review of family resilience factors identified family communication (i.e., clarity, open emotional expression, and collaborative problem solving) as one essential tool promoting family resilience (Black & Lobo, 2008;Walsh, 2016). Family resilience promotes Indigenous health equity (Burnette, 2018;Burnette & Hefflinger, 2016;Burnette, Renner, & Figley, 2019;Burnette, Roh, et al, 2019;McKinley, Lesesne, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%